2010
DOI: 10.14260/jemds/2014/2172
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE STUDY FOR ESTIMATION OF FETAL WEIGHT BY CLINICAL & ULTRASONOGRAPHICAL METHODS IN TERM PATIENTS

Abstract: BACKGROUND: Accurate determination of fetal birth weight prior to delivery can have significant bearing on management decision in labor, thereby markedly improving perinatal outcome. OBJECTIVE: To assess fetal weight in term pregnancy by different clinical and ultrasonographical methods. MATERIALS AND METHODS: The study was conducted in Obstetrics and Gynecology department of Dr. D.Y. Patil Medical College, Pimpri, Pune. Two hundred (200) women were selected and studied for a period of one year based on conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…2900 grams, thus stating that the clinical method could be taken as reliable predictor for estimation of fetal weight. 9 There was overestimation of fetal weight by Johnson's formula in 64.3% and by ultrasound in 39.3% of cases in low birth weight babies in the present study. In birth weight between 2500 to 3500 grams, Johnson's formula predicted 98.1% and ultrasound predicted 77.1% cases accurately, while in birth weight above 3500 grams, Johnson's formula predicted accurately in 79.5% of cases with underestimation in 20.5% of cases, while ultrasound predicted accurately in only 41% cases with underestimation in 59% cases.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…2900 grams, thus stating that the clinical method could be taken as reliable predictor for estimation of fetal weight. 9 There was overestimation of fetal weight by Johnson's formula in 64.3% and by ultrasound in 39.3% of cases in low birth weight babies in the present study. In birth weight between 2500 to 3500 grams, Johnson's formula predicted 98.1% and ultrasound predicted 77.1% cases accurately, while in birth weight above 3500 grams, Johnson's formula predicted accurately in 79.5% of cases with underestimation in 20.5% of cases, while ultrasound predicted accurately in only 41% cases with underestimation in 59% cases.…”
Section: Discussioncontrasting
confidence: 57%
“…2,8 Few others indicated that clinical method was simple and more reliable than ultrasound. 9 Clinical estimation of fetal weight is, therefore, an important and necessary skill in the management of obstetric patients in developing countries because of its simplicity in low resource settings as sophisticated instrument like ultrasound is not available everywhere. 1,2 Hence, the study was conducted to assess the fetal weight clinically by Johnson's formula and by ultrasound using Hadlock's formula at term and correlating it with the birth weight of the baby.…”
Section: Introductionmentioning
confidence: 99%